2021
DOI: 10.1093/alcalc/agaa143
|View full text |Cite
|
Sign up to set email alerts
|

Does Advice Based on Biomarkers of Liver Injury or Non-Invasive Tests of Liver Fibrosis Impact High-Risk Drinking Behaviour: A Systematic Review With Meta-analysis

Abstract: Background and Aims Alcohol dependence affects over 240 million people worldwide and attributed to 3 million deaths annually. Early identification and intervention are key to prevent harm. We aim to systematically review literature on the effectiveness of adding advice based on biomarkers of liver injury or non-invasive tests of liver fibrosis (intervention-based advice) to prevent alcohol misuse. Methods Electronic search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Supplementing liver function tests with NITs to stratify the severity of liver disease in high-risk areas such as community alcohol services can significantly enhance the early-detection rate [ 22 , 30 , 31 ]. Similar changes in alcohol consumption in response to NITs of liver disease have been previously reported in patients with hazardous alcohol consumption in primary and secondary care but not in community alcohol services [ 22 , 23 , 32 ]. This change in alcohol consumption is backed up by previous evidence showing that providing personalised health care communications enhances the motivation to overcome addictive behaviour [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Supplementing liver function tests with NITs to stratify the severity of liver disease in high-risk areas such as community alcohol services can significantly enhance the early-detection rate [ 22 , 30 , 31 ]. Similar changes in alcohol consumption in response to NITs of liver disease have been previously reported in patients with hazardous alcohol consumption in primary and secondary care but not in community alcohol services [ 22 , 23 , 32 ]. This change in alcohol consumption is backed up by previous evidence showing that providing personalised health care communications enhances the motivation to overcome addictive behaviour [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 71%
“…This is known to be the most effective way of preventing liver disease progression [ 21 ]. Providing feedback to patients based on NITs of liver disease can impact drinking behaviour [ 22 , 23 ]. It has been hypothesised that the demonstration of the degree of liver damage related to excess drinking, combined with advice to reduce alcohol consumption, would be more effective [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary to the social stigma associated with smoking, patients are reluctant to engage with their physicians about the hazards of smoking [26]. However, CHD prevention has no such social stigma, and recent work with biomarkers of hepatic injury has shown the benefit of physicians conveying similar information about the protective effects of alcohol cessation on liver function to patients with alcohol dependence [27]. Using potential effects of smoking cessation on CHD risk, alone or together with incentive-based programming methods for smoking cessation, could be a powerful motivator to persuade nicotine-dependent smokers to quit [16].…”
Section: Discussionmentioning
confidence: 99%
“… 15 16 Moreover, a recent systematic review suggested providing feedback to patients based on markers of liver injury can be an effective way to reduce harmful alcohol intake. 17 Access to recovery stories can help address mental health problems and support recovery from addiction. 18 19 Peer support from people who have recovered from alcohol misuse is beneficial in modifying high risk drinking behaviour.…”
Section: Introductionmentioning
confidence: 99%